Les Israéliens nombreux à Djerba pour le pèlerinage juif de la Ghriba - Lamloum, Imed (AFP, 2005)
Keywords: Judaïsme -- Djerba

Djerba, la Jérusalem d’Afrique, icône de la tolérance - Schneider, Bernard-Olivier (Le Nouvelliste, 2005)
Keywords: Judaïsme -- Djerba

L'horizon culturel des Juifs d'Afrique du Nord : une réalité chatoyante - Valensi, Lucette (Les cultures des Juifs: Une nouvelle histoire, 2005)
Keywords: Judaïsme -- Djerba

Parallels between the notation of Ovadiah Hager and a psalmodic cantillation transmitted in the oral tradition of the Jews of Djerba - Flender, Reinhard D. (Giovanni-Ovadiah da Oppido, proselito, viaggiatore e musicista dell'età normanna: atti del convegno internazionale, Oppido Lucano, 28-30 marzo 2004, 2005)
Keywords: Judaïsme -- Djerba; Musique -- Djerba

La Griba de Djerba, Tunisie - Hagiage, Liliane (2005)
Keywords: Judaïsme -- Djerba

Un Tesoro Escondido En Djerba - Kohan, Horacio (Raíces: Revista Judía de Cultura, 2005)
Keywords: Judaïsme -- Djerba

Personal Narratives as a Peacebuilding Tool: A Study of Djerbien Jewish and Muslim Co-existence - Robana, Aida (Capstone Collection, 2005)
Throughout my life, my Djerbien grandmothers emphasized the importance of storytelling and of recording the oral history of their small Tunisian island. Djerba is unique in many ways, not least of which is its thriving community of Muslims and Jews who have lived together in peace for centuries. Particularly considering the deep-seeded conflicts between people of these two religions in other parts of the world, I wanted to explore how Djerbiens have used narratives to create and maintain a culture of co-existence. I engaged in in-depth interviews with eight residents of El Hara Esseghira and El Hara Kebira, two Djerbien communities where Muslims and Jews have lived together for over a millennium. Three major themes were revealed in the course of the research: kinship, communal relations, and social identity. The data collected from in-depth interviews, informal interviews, and observation help to explain the co-existence that is prevalent on the island, and can serve as inspiration to diverse communities throughout the world struggling to co-exist. This study will also aid in preserving the richness that exists within Djerbien identity and culture while demonstrating how narratives contribute to a culture of co-existence within their community.
Keywords: Judaïsme -- Djerba